Quantitative Morphological Changes of the Choroidal Vasculature in Normal Aged and Diseased Human Donor eyes - Swathi Kanduri (Indonesian Vitreoretinal Society, 2021)
Introduction: To analyze whether the choriocapillaries undergo degenerative changes with age and disease. Corrosion casts of choroidal vessels in human donors were investigated by scanning electron microscopy (SEM) to understand the vasculature changes with age.Method: The patterns of blood vessels, vortex veins, ciliary arteries placements, capillaries placement from centre to periphery in different quadrants and regions of choroid were evaluated in twenty donor normal tissues aged from 20-90 years. Nine donors had diabetic donor tissues were evaluated in which different quadrants with laser marks and loss of blood vessels were quantified along with, six donors with signs of age-related macular degeneration were evaluated using a light stereoscopic dissection microscope. Six human donors were investigated by SEM of which two tissues were normal, two had diabetic retinopathy and two presented with age related macular degeneration changes. Result: The quantitative evaluation revealed that in normal to diseased there is a decrease of the blood vessel density in comparison to the total area of the choroid. There was also slight decrease from to centre to periphery in the % area of the blood vessel placement. Morphological identification noted was a greater number of vortex veins were noted in inferior end than the superior end. There was prominent loss of blood vessel bed was noted beneath the lasered areas in diabetic retinopathy tissues. Conclusion: Loss of % area of blood vessel density was directly correlating with the progression of age and in diabetic retinopathy diseased tissues we noted prominent loss of blood vessels underneath the laser treated areas. In age related macular degeneration, loss of blood vessels was prominent in different quadrants with age too.